Monogenic diabetes - Kavvoura, FK; Owen, KR (Elsevier, 2018)
Whereas most people with diabetes mellitus have type 1 (T1DM) or type 2 (T2DM) diabetes, there are a number of other inherited forms of diabetes and insulin resistance syndromes, which represent up to about 5% of all cases of diabetes. Monogenic forms of pancreatic β-cell dysfunction include maturity-onset diabetes of the young (MODY) and neonatal diabetes (NDM), with MODY being the most common form of inherited diabetes. The long-term response to sulfonylurea drugs in MODY caused by HNF1A and HNF4A mutations and NDM caused by KCNJ11 and ABCC8 mutations is an excellent example of pharmacogenetics. Mitochondrial diabetes is maternally inherited and usually associated with sensorineural deafness and other neurological features. Monogenic severe insulin resistance can be divided into adipose tissue defects (lipodystrophies, characterized by abnormal fat distribution) and disorders of insulin signalling. Molecular diagnosis of inherited diabetes has important implications for patients, allowing personalized management and screening of their relatives. Misclassification of monogenic diabetes or severe insulin resistance as T1DM and T2DM is common, and new tools for prioritizing suspected cases for genetic testing are needed.